Irish Gaelic in Newfoundland, reported by The Newfoundland Herald - Mannion,Maura (1991)
The history of Irish Gaelic language in Newfoundland. It was used in 18th century and declined during the next hundred years, until was totally extinction by World War I. But there were still Gaelic speakers in some cases. Aloysius was of them even today and probably the last Gaelic speaking Irish Newfoundlander.